(v-4)(v+5)=0

Simple and best practice solution for (v-4)(v+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-4)(v+5)=0 equation:


Simplifying
(v + -4)(v + 5) = 0

Reorder the terms:
(-4 + v)(v + 5) = 0

Reorder the terms:
(-4 + v)(5 + v) = 0

Multiply (-4 + v) * (5 + v)
(-4(5 + v) + v(5 + v)) = 0
((5 * -4 + v * -4) + v(5 + v)) = 0
((-20 + -4v) + v(5 + v)) = 0
(-20 + -4v + (5 * v + v * v)) = 0
(-20 + -4v + (5v + v2)) = 0

Combine like terms: -4v + 5v = 1v
(-20 + 1v + v2) = 0

Solving
-20 + 1v + v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(-5 + -1v)(4 + -1v) = 0

Subproblem 1

Set the factor '(-5 + -1v)' equal to zero and attempt to solve: Simplifying -5 + -1v = 0 Solving -5 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1v = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1v = 0 + 5 -1v = 0 + 5 Combine like terms: 0 + 5 = 5 -1v = 5 Divide each side by '-1'. v = -5 Simplifying v = -5

Subproblem 2

Set the factor '(4 + -1v)' equal to zero and attempt to solve: Simplifying 4 + -1v = 0 Solving 4 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1v = 0 + -4 -1v = 0 + -4 Combine like terms: 0 + -4 = -4 -1v = -4 Divide each side by '-1'. v = 4 Simplifying v = 4

Solution

v = {-5, 4}

See similar equations:

| 3x-6=x/10 | | X+X(.25)=180 | | 5(2x-5)=9(x+2) | | x+5/11=8/17 | | -3(r-8)=-36 | | 7x-1=4x | | 13+1/4y | | 5x^3-26x^2+5x=0 | | 0=x^4+2x^3+x^2 | | -4/3x+4/9+x^2=0 | | (3.15)(2.4)=r | | 1/4y+13 | | (-0.111)(0.12)=p | | 25y^5+12y^4= | | 473+286N=943 | | X^2+(m-8)x+m=0 | | (2.18)3.4=z | | -2/3-1=5/6 | | 85+7m=1955 | | w^2+3W+2.25=8 | | -29.95-5.50x= | | 12x^2+43x+15=0 | | k=400(-8.15) | | 6x+6=2x-4 | | 7D=105 | | 6(x-4)-19=23-(x+5) | | 4x-5b=4c | | 8x^2+7=5x^2+4 | | 4x+27=3x+0 | | -3-4(2d-3)=4 | | (-3.2)(-8.61)=f | | Y/2=56 |

Equations solver categories